"The Common Law is … not what it used to be"*: Revisiting Recognition of a Constitutionally-Inspired Implied Duty of Fair Dealing in the Common Law Contract of Employment (Part 2): Revisiting the Recognition of a Constitutionally-Inspired Implied Duty of Fair Dealing in the Common Law Contract of Employment - Part 2 - Louw, Andre (Potchefstroom Electronic Law Journal, 2018)
This piece, which is in three parts, will revisit the importation of fairness into the employment contract (outside and independent of the fairness-based provisions of our labour legislation) by a line of Supreme Court of Appeal (SCA) judgments during the 2000s. This process culminated in the recognition of an "implied duty of fair dealing" in the common-law employment contract. This piece will discuss such developments, will argue that such an implied duty still forms part of our law (despite the apparent consensus in the literature that the SCA turned its back on such earlier judgments), will critically examine some of the arguments for and against the recognition of such a duty, and will then consider the issue within the broader context of the role of good faith and fairness in our general law of contract.